Comparative Analysis of The Financial Ratios of LQ45 Index Companies Before and During The Covid-19 Pandemic: Analisis Komparasi Rasio Keuangan Perusahaan Indeks LQ45 Sebelum dan Saat Pandemi Covid-19 - Pambudianna, Badzliah A Ghaisani; Sari, Herlinda Maya Kumala (Indonesian Journal of Innovation Studies, 2022)
Based on statistical data from the Indonesia Stock Exchange, the declinein stock price occured very drastically in March 2020, in wich month the Covid-19 case was first announced in Indonesia. All sectors experienced a decline due to the impact of this pandemic, including companies that are members of the LQ45 index. There are differences in speculation about the loss or profit of the LQ45 index company during the Covid-19 pandemic, so this research is carried out to prove the LQ45 index company has an impact on their financial performance due to the current pandemic or not.The sample used is 35 companies that are members of the LQ45 index. The type of research used is a comparative study with a quantitative approach. The analytical tools used are liquidty ratios, activity ratios, solvency ratios, profitability ratios, and market ratios wich are tested differently by paired sample t-test and wilcoxon signed rank test.The result of the different test with the paired sample t-test show that there are differences in the Current Ratio, Debt to Asset Ratio, and Debt to Equity Ratio. Meanwhile, the wilcoxon signed rank test show that there are differences in Total Asset Turnover, Return On Asset, and Price Earning Ratio. This proves that the LQ45 index company is also affected by the pandemic, even though it is called the most liquid company listed on the IDX.